PERSAMAAN DAN PERBEDAAN UNSUR LOGAM BENDA-BENDA PERUNGGU SUMATERA BAGIAN UTARA DENGAN BENDA-BENDA PERUNGGU JAWA TENGAH: ANTARA KEMANDIRIAN TEKNIS DAN PEMENUHAN KONSEP - Ery Soedowo (Berkala Arkeologi, 2012)
When India culture introduce to Indonesia Archipelago, some changes were happen in its native culture. One of India influence was its religion i.e. Hinduism and Buddhism. Both religion then resemblance in material culture such as sacred building (temple), rites utensils (statue, bell, monk stick finial, etc.), or inscription. One of its material source to made those things is bronze. When Indian culture was introduced, the natives weren’t take it for granted adopt Indian concept for producing bronze things. By XRF analysis, known that bronze artifacts from Northern Sumatra and Java aren’t adopt concept from India traditions i.e. astadhatu and pancaloha. Indian influence on bronze artifacts from Northern Sumatra and Java can see on fullfilness of religion concept, especially on statues. It seen on the choosing of special metals as dominan elements for bronze statue construction. This study reveals some of similarities and diverences in construction elements between Northern Sumatra and Java bronze artifacts.